Paul Ricoeur’s search for recognition - Vargas Bonilla, Edwin Alonso (Disertaciones, 2020)
The following article makes a brief course into de philosophical paths followed by the french thinker Paul Ricoeurs as he searchs for the meaning of the concept of recognition. The guiding question to value the contribution of Ricoeur is: how to surpass the emptyness of the concept of recognition in the philosophical scope? Three moments will be explored to fullfil this purpose: identiy as a background, the development of its idea, and is final political and philosophical meaning. This path offers an alternative proposal to surpass the empty space given tho this term along the history of ideas, opening a way to the development of a philosophical theory of recognition with an independent status.